Optimization of boron dispersion on ﬁbrous-silica-nickel catalyst for enhanced CO2 hydrogenation to methane - Nurul Sahida, Hassan; Aishah, Abdul Jalil; Nor Aiza, Abdul Fatah; Hussain, Ijaz; Rahman, A. F.A.; Dolit, S. A.M.; Kamarizan, Kidam; Rahimah, Jusoh; Muhammad Arif, Ab Aziz; Herma Dina, Setiabudi; Cheng, Chin Kui (Elsevier Ltd, 2022)
There are numerous reports regarding boron-containing catalysts for hydrogen-related reactions from CO2 including dry reforming of methane and methanation. Besides enhancing the productivity, boron also improved nickel activity and stability. However, the detailed mechanistic study, particularly in explaining the starring role of boron in the enhanced reactions, is still lacking. Thus, herein we loaded boron on fibrous-silica-nickel and investigated their physicochemical properties and mechanistic route by means of in-situ FTIR for enhanced CO2 methanation. It was found that the appropriate dispersion of boron surrounds the nickel particles is an important factor to improve the adsorption of CO2 before interacting with split hydrogen atom from the nickel sides to form intermediates which are subsequently dehydrated, and then serial hydrogenation gave the final product of methane. Boron also accelerated the methanation and restricted coke formation. A hybrid approach on optimization via a face-centered central composite design and a response surface methodology showed that reaction using H2/CO2 ratio of 6, GHSV of 10,500 mL g−1 h−1, at 500 °C gave the highest percentage of CH4 of 84.3%. To indicate the error, the predicted values were compared to the experimental values, yielding an accurately minimal error ranging from 0 to 11%. As a result, the empirical models generated for CO2 hydrogenation to methane were reasonably accurate, with all actual values for the confirmation runs fitting within the 94% prediction interval.